Assessing the Correlation between Demographics, Academic Stress, and Coping Strategies of Filipino High School Students with Single-Parents - Kenia Hukom; Dennis Madrigal (Philippine Social Science Journal, 2020)
Academic stress is a certain level of academic-related demands that exceed the students' adaptive capabilities. Related to this is coping strategies, which is a mindful effort to endure the stress. Thus, the descriptive-correlational research determined the associations among the demographic variables, the level of academic stress, and the extent of coping strategies. Academic Stress Scale and COPE Inventory standardized tests, were used among sixty-seven Filipino high school students with single-parents of a Catholic school. The data were statistically analyzed using Mean, Standard Deviation, Pearson r, and Spearman rank correlation. As a whole, their academic stress is low with no significant relationship between academic level and single-parents' educational level.  However, a moderate level of academic stress was found with a significant relationship between sex and family monthly income. The overall coping strategies is great with a significant relationship between family monthly income. However, there is no significant relationship between coping strategies and academic level, sex, and single-parents' educational level. Finally, no significant relationship was found between academic stress and coping strategies. The study recommends designing an enhanced stress management program for high school students.